The Influence of Problem Based Learning Model on Cognitive Learning Outcomes of Mathematics in Grade V Elementary School Students - Simamora, Ebeneser Wacner; Haryanto; Siboro, Asiroha; Siahaan, Fitriani (Jurnal Elementaria Edukasia, 2025)
Increasing the effectiveness of the learning process can be realized through the application of learning models that are in line with student characteristics. One approach that supports active student involvement is the Problem Based Learning model. This study aims to analyze the effect of the application of the Problem Based Learning model on the achievement of cognitive learning outcomes in mathematics subjects in grade V students at the elementary school level. This study uses a quantitative approach with a Pre-Experimental design, specifically the One-Group Pretest-Posttest Design type. The research subjects included all grade V students of SD Negeri 02 Amban as many as 32 students in the 2024/2025 academic year. Data analysis techniques involve normality tests, t-tests, and n-gain tests, with the help of SPSS software version 30. The results of the normality test show that the pretest value data (0,123 > 0,05) and posttest (0,105 > 0,05) are normally distributed. Meanwhile, the t-test showed a significant difference between the pretest and posttest scores with a significance value (2-tailed) of 0,001 (p < 0,05), indicating that there was a significant increase in cognitive learning outcomes after the implementation of the PBL model. Based on the significance value (0,001 < 0,05), the null hypothesis (H0) was rejected and the alternative hypothesis (H1) was accepted. In addition, the results of the n-gain analysis showed an increase in the average score from 64,44 to 84,09 with a difference of 19,66 points, and the average n-gain value was 0,56, which was categorized as quite effective. Thus, the results of this study indicate that the implementation of the Problem Based Learning model has a positive effect on improving the cognitive learning outcomes of elementary school students in mathematics.